1998
DOI: 10.1002/(sici)1521-396x(199804)166:2<835::aid-pssa835>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron Trapping in Acceptor Doped Polymers

Abstract: Eletron mobilities have been measured in N,N′‐bis(1,2‐dimethylpropyl)‐1,4,5,8‐naphthalenetetracarboxylic diimide (NTDI)‐doped poly(styrene) containing a series of acceptor traps with depths between 0.11 and 0.41 eV. The results are explained within the framework of a formalims based on disorder. The formalism is premised on the assumption that charge transport occurs by hopping through a manifold of localized states that are distributed in energy. The key parameter of the formalism is σ, the energy width of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Furthermore, the dye concentration in such systems typically ranges from 1 to 10%. Figure 3, and also previous experimental work [9][10][11][12][13][14][15], shows that the cross-over to guest-to-guest hopping can coincide with this concentration range.…”
Section: Small Electric Fields-comparison With Semi-analytical Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the dye concentration in such systems typically ranges from 1 to 10%. Figure 3, and also previous experimental work [9][10][11][12][13][14][15], shows that the cross-over to guest-to-guest hopping can coincide with this concentration range.…”
Section: Small Electric Fields-comparison With Semi-analytical Resultssupporting
confidence: 80%
“…The charge-carrier mobility in host-guest systems is substantially influenced by the guest if the energy of the HOMO (highest occupied molecular orbital) and/or LUMO (lowest unoccupied molecular orbital) of the guest molecule lies within the energy gap of the host. Time-of-flight (TOF) experiments [9][10][11][12][13][14][15] have revealed that there are then four transport regimes (see figures 1(a)-(d)). For very small guest concentrations the presence of guest molecules will not significantly affect the charge transport (figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%
“…Arenediimide groups were chosen for single‐electron islands due to their strong electron acceptor properties. (They have already been exploited in the design of a variety of molecular materials 41–4546.…”
Section: Molecular Devicesmentioning
confidence: 99%